4 can go in 66 sixteen times
Answer:
Step-by-step explanation:
O
3x² - 11x - 4 = 0
a = 3 ; b = -11 , c = -4
![Sum \ of \ roots = \dfrac{-b}{a}=\dfrac{-(-11)}{3}=\dfrac{11}{3}\\\\Product \ of \ roots =\dfrac{c}{a}=\dfrac{-4}{3}\\\\](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-b%7D%7Ba%7D%3D%5Cdfrac%7B-%28-11%29%7D%7B3%7D%3D%5Cdfrac%7B11%7D%7B3%7D%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%5Cdfrac%7Bc%7D%7Ba%7D%3D%5Cdfrac%7B-4%7D%7B3%7D%5C%5C%5C%5C)
W
8x² + 12x = -1
8x² + 12x + 1 = 0
a = 8 ; b = 12 ; c = 1
![Sum \ of \ roots =\dfrac{-b}{a}=\dfrac{-12}{8}=\dfrac{-3}{2}\\\\Product \ of \ roots = \dfrac{c}{a}=\dfrac{1}{8}](https://tex.z-dn.net/?f=Sum%20%20%5C%20of%20%5C%20roots%20%3D%5Cdfrac%7B-b%7D%7Ba%7D%3D%5Cdfrac%7B-12%7D%7B8%7D%3D%5Cdfrac%7B-3%7D%7B2%7D%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7Bc%7D%7Ba%7D%3D%5Cdfrac%7B1%7D%7B8%7D)
L
x² + x = 6
x² + x - 6 = 0
a = 1 ; b= 1 ; c = -6
![Sum \ of \ roots = \dfrac{-1}{1}=-1\\\\Product \ of \ roots = \dfrac{-6}{1}=-6](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-1%7D%7B1%7D%3D-1%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-6%7D%7B1%7D%3D-6)
G
x²- 2x - 2 =0
a = 1 ; b = -2 ; c = -2
![Sum \ of \ roots = \dfrac{-(-2)}{1}=2\\\\Product \ of \ roots = \dfrac{-2}{1}=-2](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-%28-2%29%7D%7B1%7D%3D2%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-2%7D%7B1%7D%3D-2)
E
4x - 5 = -4x²
4x² + 4x - 5 = 0
a = 4 ; b = 4 ; c = -5
![Sum \ of \ roots = \dfrac{-4}{4}=-1\\\\Product \ of \ roots=\dfrac{-5}{4}](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-4%7D%7B4%7D%3D-1%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20%20roots%3D%5Cdfrac%7B-5%7D%7B4%7D)
B
12x² +x -6 = 0
a = 12 ; b = 1 ; c = -6
![Sum \ of \ roots =\dfrac{-1}{12}\\\\Product \ of \ roots =\dfrac{-6}{12}=\dfrac{-1}{2}](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%5Cdfrac%7B-1%7D%7B12%7D%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%20%3D%5Cdfrac%7B-6%7D%7B12%7D%3D%5Cdfrac%7B-1%7D%7B2%7D)
R
2x² + 5x - 25 = 0
a = 2 ; b = 5 ; c = -25
![Sum \ of \ roots=\dfrac{-5}{2}\\\\Product \ of \ roots =\dfrac{-25}{2}](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%3D%5Cdfrac%7B-5%7D%7B2%7D%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%5Cdfrac%7B-25%7D%7B2%7D)
A
6x² -5x - 4 = 0
a = 6 ; b = -5 ; c = -4
![Sum \ of \ roots =\dfrac{-[-5]}{6}=\dfrac{5}{6}\\\\Product \ of \ roots = \dfrac{-4}{6}=\dfrac{-2}{3}](https://tex.z-dn.net/?f=Sum%20%5C%20of%20%5C%20roots%20%3D%5Cdfrac%7B-%5B-5%5D%7D%7B6%7D%3D%5Cdfrac%7B5%7D%7B6%7D%5C%5C%5C%5CProduct%20%5C%20of%20%5C%20roots%20%3D%20%5Cdfrac%7B-4%7D%7B6%7D%3D%5Cdfrac%7B-2%7D%7B3%7D)
Answer:
The slope is -1/2 or -0.5
Hope this helps!
Answer:
n<7
Step-by-step explanation:
hope i did okay for you